Regulation without the state: The example of financial services - Philip Booth (Institute of Economic Affairs (IEA), 2019)
There are frequent calls for financial markets to be more actively regulated by state agencies, such as the Financial Conduct Authority or the Prudential Regulation Authority. They reflect neo-classical, market-failure approaches to economics, which suggest that the market does not maximise welfare if certain conditions do not hold and that government action is required to move the market towards the welfare-maximising position. But we cannot know whether government regulatory action will move us away from or towards the welfare-maximising position unless we also make unrealistic assumptions about behaviour in regulatory agencies. The neo-classical, market-failure approach therefore takes us down an intellectual rabbit hole. It is instead possible to think of regulation as part of the set of services provided by the market, rather than something that to be done to the market ex-post. The discovery of regulatory organisations is part of the entrepreneurial market process. Regulatory institutions evolving within the market continue to evolve, despite the attempts by government agencies to regulate markets in very detailed ways. Modern examples would include the International Swaps and Derivatives Association (ISDA), whose record during the financial crisis was faultless. There are disadvantages arising from private regulatory bodies: they can encourage cartelistic behaviour and may prove less effective where the economic activity in question gives rise to widespread social costs beyond market participants. However, we should reject market failure analysis and operate under the assumption that the market can provide regulatory services because they are valued by market participants. Where statutory regulation is used, it should generally be voluntary with products not regulated by the statutory regulator being clearly identified as such.
Keywords: G18; G28; H12; H11; H30; E60; M48; I30; 330